Integration of Media Literacy in Religious Counseling for Preventing Early Marriage in Nias Barat - Sampurna, Ahmad; Ritonga, Hasnun Jauhari; Matondang, Abdul Rahman (The Islamic Education and Multiculturalism Foundation, 2024)
Early marriage remains a significant social challenge in Nias Barat, driven by cultural norms, economic pressures, and limited access to education. Religious counseling has long been a key strategy in addressing this issue, leveraging the influence of religious leaders to raise awareness about its risks. However, traditional counseling methods often fail to engage younger generations effectively, particularly in the digital era. This study explores the integration of media literacy into religious counseling as a transformative approach to preventing early marriage. Using a qualitative descriptive method with elements of Community-Based Research (CBR), data was collected through in-depth interviews, focus group discussions, and participatory observation involving religious counselors, parents, youth, and community leaders. The findings reveal that while religious counseling holds significant potential, its impact is limited by infrastructural, generational, and cultural barriers. Integrating media literacy offers opportunities to modernize these efforts, enhancing their relevance and reach. Community-based strategies that actively involve stakeholders in creating and disseminating culturally sensitive media content emerged as a promising approach. Despite challenges such as limited digital infrastructure and financial constraints, this integration fosters collaboration and ensures sustainability. This study contributes to the academic discourse on early marriage prevention by highlighting the importance of combining traditional practices with modern innovations. The results offer practical recommendations for policymakers and practitioners, providing a scalable model for similar contexts in Indonesia and beyond.